Faktor Penyebab Kurangnya Minat Guru Memanfaatkan Perpustakaan SDN 09 Air Tawar Barat - Linalti, Lisa; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper discuss about factors that cause a lack of the teacher's role to Library of SDN 09 Air Tawar Barat. The purpose of this paper is: (1) describe the teacher's perception of the Library of SDN 09 Air Tawar Barat, (2) describe the factors that cause a lack of participation in the school library. The research methodology used a qualitative approach. Data was collected through observation and interviews. The interviews were conducted to teachers structured guided. Data was analyzid by: (1) describe the results of the interviews, (2) obtained in accordance with the theories discussed, (3) conclusions and (4) reporting. Based on analyzing the data it can be concluded: (1) teachers do not know the function of the library, (2) a collection of books in the library is not in accordance with the curriculum that is used in teaching and learning, (3) teachers tend to assign students the task of looking on the internet rather than using books existing library, (4) library interior uncomfortable so make teachers and students not visited the library and, (5) BOS funds are not used for library purposes. Collections of the Library of SDN 09 Air Tawar Barat can not meet the needs of teachers and students as seen collections of the library is not in accordance with the curriculum that is used in teaching and learning and a collection of books that are available most obselent. From this fact, teachers and students do not utilize the book in the library. The library can not meet the needs of teachers and students. Keywords: lack of using the library;Â teacher; students.